Composition of the Essential Oil of Endemic Psephellus pyrrhoblephara Boiss. (Asteraceae) From Turkey - Hayta, Sukru; Bagci, Eyup (Taylor & Francis Ltd, 2015)
The essential oil obtained by hydrodistillation from endemic Psephellus pyrrhoblephara Boiss. (Asteraceae) from Turkey was analyzed by GC and GC-MS system. Thirty nine components in aerial parts of Psephellus pyrrhoblephara were identified, representing 87.0 % of the oils. The main constituents of the oil were found as 8,9-dihydroneolongifolene, (27.0 %), 9,10-dehydroisolongifolene, (10.8 %), Decahydronaphthalene, (10.6 %), and beta-caryophyllene (6.5 %). The results were discussed with the genus pattern in terms of chemotaxonomy and natural products.
Keywords: endemic; 8,9-dihydro neolongifolene; essential oil; Asteraceae; Psephellus pyrrhoblephara